Pathological prognostic factors in prostate cancer - Cohen, Ronald Joseph (My University, 1991)
Adenocarcinoma of tbe prostate is the commonest cancer of the western male. Each year more than 120 000 new cases are reported in the United States alone, together with more than 26 000 deaths. Autopsy studies suggest that the majority of prostatic cancer remains clinically undetected, therefore propagating the concept of latent versus aggressive disease. [Abbreviated Abstract. Open document to view full version]
A thesis submitted to the Faculty of Medicine, University of the Witwatersrand, for the degree of Doctor of Philosophy in Medicine.
Keywords: Prostatic Neoplasms